Produção, caracterização e avaliação de nano e micropartículas de ácido ascórbico para fins odontológicos - Telles, Íris Sol Figueiredo. (2018)
This study aimed to produce and characterize nano and microparticles (NP-MP) of ascorbic acid (AA) to increase the stability of the drug and to develop antioxidant solutions to be used prior to the sealing of fiberglass pins to dentin. The AA was encapsulated by vicillin, the green pea protein, through the spray drying technique. The particles were characterized through SEM, AFM, XRD, FTIR and the release of AA was evaluated through UV-Vis. The antimicrobial activity was evaluated by ágar diffusion technique with E. faecalis and C. albicans. Finally, 50 roots of human premolars received endodontic treatment. Preparation was made for 10mm pin, followed by irrigation of the conduit with 0.5%, 1%, 1.5% solution of NP-MP of AA in acidified distilled water or 10% of sodium ascorbate (AS), and then the pins were sealed. The pins bond resistance was evaluated through the push-out test. The NP-MPs prove efficient encapsulation and release of AA, but presented lower resistance bond values when compared to acidified distilled water and AS. Through SEM it was possible to observe particles of 10 to 1 mm. However, through the AFM were found nanoparticles of 50 to 2 nm. The development of NP-MP systems has great potential for AA protection, but they negatively interfere in the bond resistance of fiberglass pins to the intraradicular dentin.